2015
DOI: 10.5435/jaaos-d-14-00019
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Management of Early-onset Scoliosis

Abstract: Early-onset scoliosis is potentially fatal if left untreated. Although surgical management with growing instrumentation may be necessary, this is not a panacea and is associated with high complication rates. Recent evidence has demonstrated that nonsurgical treatment can be an effective early management strategy in delaying or even precluding the need for surgery, especially surgery with growing instrumentation. The goal of both nonsurgical and surgical management is to control or correct the spinal curve to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…5 The most common causes of EOS are idiopathic, congenital, neuromuscular, or syndromic. 6 The deformity may inhibit the development and function of the heart and lungs, representing 2 of the most severe consequences of EOS. [7][8][9] According to the etiology and evolution of the disease, motor function impairment of the patient is observed, with a consequent decrease in recreational activities and routine activities, such as brushing and bathing, and a compromise of cardiopulmonary, intestinal, and bladder function, together with intense pain.…”
Section: Introductionmentioning
confidence: 99%
“…5 The most common causes of EOS are idiopathic, congenital, neuromuscular, or syndromic. 6 The deformity may inhibit the development and function of the heart and lungs, representing 2 of the most severe consequences of EOS. [7][8][9] According to the etiology and evolution of the disease, motor function impairment of the patient is observed, with a consequent decrease in recreational activities and routine activities, such as brushing and bathing, and a compromise of cardiopulmonary, intestinal, and bladder function, together with intense pain.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous resolution of IS has been observed in cases with the “benign” form [19]. In contrast, the natural history of non-idiopathic early onset scoliosis is usually progressive.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 56% of orthopaedists take the first in-cast radiograph in the supine position, while the rest take it with the patient standing and awake. The distinction is important because major curve angles are smaller in supine than standing radiographs, 9 preventing accurate comparison between patients in different positions. However, it is important to consider the age and diagnosis of the patient population, which cause natural variations in ambulatory ability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of cast treatment for long congenital curves with multiple anomalous vertebrae found thoracic growth rate was slower than normal, 11 but that T1-T12 height increased significantly over treatment. 12 Neuromuscular patients often have respiratory and gastrointestinal co-morbidities, 9 but their cast treatment outcomes have been described. 6 , 7 , 10 , 13 - 15 In general, they are found to attain less major curve angle correction 16 and greater correction loss after cast removal than idiopathic patients.…”
Section: Discussionmentioning
confidence: 99%